Efektifitas Pelatihan Harga Diri Dengan Metode Instruksi Diri Untuk Meningkatkan Kepercayaan Diri Pada Siswa Bbrsbd Surakarta - SURYANINGRUM, DIAN ULFA; , Dr. Nanik Prihartanti,M.Si., Psi; , Wisnu Sri Hertinjung,S.Psi.,M.Psi (2016)
This study aims to look at the effectiveness of self-esteem training with instruction methods themselves on disability in Surakarta BBRSBD 2015 and to determine the level of self-esteem in disabled people before and after treatment. The subjects were 24 kalayan, 12 kalayan in the experimental group and 12 in the control group kalayan. Characteristics of the subjects are: 1) students who score low and medium confidence, 2) aged 14-40 years, 3) minimal elementary education. The experimental group received treatment in the form of self-esteem training with self-instruction methods. While the control group did not receive treatment. The design was quasi-experimental design with design form nonequivalent control group design. Collecting data in this study was conducted using a scale of confidence. Results Wilcoxon Signed-Rank Test showed that the self-esteem training to become effective instruction method improves confidence kalayan (p = 0.002) and a control group that was not subjected to the treatment does not increase confidence. Mann Whitney U results show that there are differences between the experimental and control groups in which the experimental group increased confidence than the control group (p = 0.000). The conclusion is that the self-esteem training to become effective instructional methods to increase confidence in kelayan BBRSBD Surakarta.